Der Lebensunterhalt der bayerischen Bevölkerung - eine wirtschaftsgeographische Planungsgrundlage - Ruppert, Karl (ERDKUNDE, 1965)
The paper discusses the most important sources of livelihood of the population of Bavaria under the aspect of establishing socio-economic areal units as a basis for planning. According to the relative importance of the primary, secondary and tertiary economic sector the individual communes were classified and by means of triangle graphs in the enclosed map accordingly cartographically represented. The data used as basis are those of the 1961 census of population and occupations. In order to be able to estimate the sources of livelihood of the entire population, incomes from rents, pensions, capital investment etc. were in addition to earned incomes also considered and where they reached a higher than average amount they have also been cartographically rep resented on map in the text. In conclusion a brief regional interpretation is given and the preparation of such economic geographical bases for planning purposes is discussed.